A simple method for the fabrication of nanomotors based on a gold nanosheet decorated with CoPt nanoparticles1. Issue 64 (12th July 2015) - Amouzadeh Tabrizi, Mahmoud; Shamsipur, Mojtaba
<x xml:space="preserve">Abstract</x> In this communication we present an extremely rapid, simple and template-free method for the electrochemical fabrication of CoPt/gold nanosheet motors (NSMs) via a three-step applied potential process.